Tantangan Pendidik Nahwu untuk Meningkatkan Kompetensi Profesional sebagai Upaya Menumbuhkan Motivasi Pembelajar Pemula terhadap Struktur Bahasa Arab - Sulaikho, Siti; Wahidmurni, Wahidmurni; Amrullah, Abdul Malik Karim (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2023)
This study seeks to uncover the challenges of nahwu educators through an exploration of the difficulties faced by beginner learner students towards nahwu and an exploration of their expectations for nahwu educators. This type of research is a mixed method by combining qualitative and quantitative sequentially and is descriptive. Data collection by observation, open interviews, and documentation. Qualitative data analysis with 3 stages of Miles & Huberman while quantitative data analysis uses percentages. The results of the exploration of difficulties showed: 1] do not know the basics in nahwu (10%), 2] distinguish the names contained in nahwu (5%), 3] understand nahwu because there is too much material in one explanation (5%), 4] understand nahwu because explanations are not sequential (5%), 5] remember Arabic vocabulary (7%), 6] remember the rules in nahwu (39%), 7] apply nahwu to examples (29%). The results of the exploration of expectations showed: 1] explained repeatedly (14%), 2] after explaining the rules and giving examples (20%), 3] then applying them to Arabic texts or scriptures (22%), 4] explanations delivered more slowly and in a relaxed atmosphere (10%), 5] using the help of audio-visual media (20%), 6] using more interactive methods in explaining nahwu (12%), 7] adding naáº“am/syi'ir nahwu then sung together, Easy to understand Nahwu references (2%). This research can be used as a foundation for nahwu educators to choose approaches, methods, and strategies in teaching nahwu for students with the same characteristics and students with different characteristics. This research is also the basis for nahwu educators to improve professional competence.